2020
DOI: 10.1007/s10551-020-04465-w
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of an Empirical Model for Islamic Corporate Social Responsibility: Evidence from the Middle East

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 125 publications
2
48
0
Order By: Relevance
“…Such a critical perspective, thereby, rationalises the necessity and emergence of ICG through the specific normative world of Islam, as having the transactions of IBs Islamic, while their governance representing the universal values creates incoherence. In a similar attempt, for example, Koleva (2020) rather than applying the universally accepted CSR checklist to determine the CSR performance of IBs, she has developed an authentic CSR frame and its constituents through the normative worldview of Islam. This paper, hence, aims to overcome the observed gap in developing an authentic ICG frame beyond hybridising the universal models to develop an ICG frame, as detailed below.…”
Section: Islamic Corporate Governance Framework and Shari'ah Boardsmentioning
confidence: 99%
“…Such a critical perspective, thereby, rationalises the necessity and emergence of ICG through the specific normative world of Islam, as having the transactions of IBs Islamic, while their governance representing the universal values creates incoherence. In a similar attempt, for example, Koleva (2020) rather than applying the universally accepted CSR checklist to determine the CSR performance of IBs, she has developed an authentic CSR frame and its constituents through the normative worldview of Islam. This paper, hence, aims to overcome the observed gap in developing an authentic ICG frame beyond hybridising the universal models to develop an ICG frame, as detailed below.…”
Section: Islamic Corporate Governance Framework and Shari'ah Boardsmentioning
confidence: 99%
“…The world countries, which are majorly based on Christian and Muslims, emphasize CSR activities and emphasize productive human activities and community-related practices (Ray et al , 2014; Cui et al , 2019). Koleva (2020) and Zinkin (2007) explored the relationship between Islam and CSR, and he concluded that in Islam, helping society with CSR advancement is a fundamental element, which can be seen from that Qur'an said: “The main purpose of the creation of mankind is special nature of worship in term of serving humanity (ibadah) .”…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Quran, as well as setting up a idea of nature in connection to God and man, also sets out an moral code to guide book to man: waste is abhorred 27 , as is arrogance and all its manifestations in boastful exhibitions of wealth. As a substitute, Islam encourages fairness and distributive justice 28 . Also there is in existence a body of Islamic source of law, courting from the period of the Prophet Mohammad (PBUH) which forbids private proprietorship of shared property resources such as grassland, wildlife, woodland and water, which should be handled for the common good.…”
Section: Islamic Perspective Of Sustainable Developmentmentioning
confidence: 99%
“…25 Illays Baker, "Flight of Time Ecology and Islam," Islam and Environment, ed. Harfiah Abdel Haleem, (London:Ta-Ha publishers, 1998):83 26 Hafiz BA al-Masri, "Islamic Concern for Animals",(Hants, UK: The Athene Trust, 1987) 27 Al-Quran 7:31 28 harnessed to the management of natural resources 29 . It is known fact that Islam promotes earning for the cause of living through hard labour which is considered as an act of worship.…”
Section: Islamic Perspective Of Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation